Hubungan Paparan Pestisida Berdasarkan Lama, Frekuensi dan Waktu Penyemprotan Pestisida Terhadap Tekanan Darah pada Petani di Desa Sumowono Kecamatan Sumowono Kabupaten Semarang - Kartika Dian Pertiwi; Ita Puji Lestari; Raid Fachri Labib; Hasna Nafiza Zalfa; Nursuwaibah; Fadhilla Viola Nita (Universitas Ngudi Waluyo, 2024)
Sumowono is a sub-district in Semarang Regency, Central Java, Indonesia. This sub-district is approximately 24 km from the capital city of Semarang Regency. Sumowono District is widely known among the people of Central Java because it is an area that produces vegetables, flowers, fruit and various plantation products. In an effort to improve the quality of agricultural products, farmers often use pesticides as an effort to reduce losses due to plant pests. These efforts make it difficult to separate farmers and pesticides. The aim of this research is to determine the relationship between length, frequency and time of pesticide spraying and blood pressure in farmers in Sumowono District. This research is an observational analytical research with a cross sectional design. The population used was farmers using pesticides in Sumowono District with a sample of 100 respondents. The sampling technique in this research used a simple random sampling method. With the research results, it was found that the P value was 0.821 > 0.05, so H0 was accepted, meaning there was no relationship between the duration of pesticide spraying and blood pressure. The P value of the frequency of pesticide spraying is 0.737 > 0.05, so H0 is accepted, meaning there is no relationship between the frequency of pesticide spraying and blood pressure. blood pressure. Thus, it can be concluded that there is no relationship between the duration of spraying, the frequency of spraying and the time of pesticide spraying with the incidence of blood pressure in farmers in Sumowono District. ABSTRAK Sumowono adalah sebuah kecamatan di Kabupaten Semarang, Jawa Tengah, Indonesia. Kecamatan ini berjarak sekitar 24 Km dari ibu kota Kabupaten Semarang. Kecamatan Sumowono dikenal luas di kalangan penduduk Jawa Tengah karena merupakan kawasan penghasil sayur mayur, bunga-bungaan, buah-buahan, dan aneka hasil perkebunan. Upaya untuk meningkatkan mutu hasil produk pertanian, petani sering menggunakan pestisida sebagai salah satu upaya untuk mengurangi kerugian akibat hama tanaman. Upaya tersebut menyebabkan petani dan pestisida menjadi sulit untuk dipisahkan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara lama, frekuensi dan waktu penyemprotan pestisida dengan tekanan darah pada petani di Kecamaatan Sumowono. Penelitian ini adalah penelitian analitik observasional dengan rancangan Cross Sectional. Populasi yang digunakan adalah petani pengguna pestisida di Kecamatan Sumowono dengan sampel sebanyak 100 responden. Teknik sampling dalam penelitian ini menggunakan metode simple random sampling. Dengan hasil penelitian didapatkan nilai P value 0,821 > 0,05 maka H0 diterima artinya tidak ada hubungan antara lama penyemprotan pestisida dengan tekanan darah. Nilai P value frekuensi penyemprotan pestisida 0,737 > 0,05 maka H0 diterima artinya tidak ada hubungan antara frekuensi penyemprotan pestisida dengan tekanan darah dan nilai p-value waktu penyemprotan pestisida 0,913 > 0,05 maka H0 diterima artinya tidak ada hubungan antara waktu penyemprotan pestisida dengan tekanan darah. Dengan demikian dapat disimpulkan bahwa tidak ada hubungan antara lama penyemprotan, frekuensi penyemprotan dan waktu penyemprotan pestisida dengan kejadian tekanan darah pada petani di Kecamatan Sumowono.